Serangan Hama Penggerek Cabang Mangga (Rhytidodera sp.) (Coleoptera: Cerambycidae) di Kelurahan Manembo-Nembo Kota Bitung - Mieke Walalangi; Max Tulung; James B. Kaligis; Caroulus S. Rante (Universitas Sam Ratulangi, 2015)
ABSTRACT The study aims to determine the percentage of the branch borer attack on mango crops in the village of Manembo-nembo, Bitung. The study lasted for six months, from July 2014 to December 2014. The study was conducted by surveys with purporsive sampling. On plant mango, symptoms were observed branches showing on that were attacked and not attacked. Mango crop was considered infected if found bored sign on branches. Observations were made on three types of mangoes namely Mango Manalagi, Arumanis, and Lilin, in which observations were conducted four times. The results showed that the mango crops Manembo-nembo were attacked by borer branches, Rhytidodera sp. The highest percentage during the four observations found on Arumanis Mango attack plants by 21.44% in the first observation, Manalagi of 16.20% at the first observations and the lowest of 9.28% on Lilin Mango in the fourth observation. Keywords : Manggo Arumanis, Manalagi, Lilin Rhytidodera sp.